NTRK testing: First results of the QuiP‐EQA scheme and a comprehensive map of NTRK fusion variants and their diagnostic coverage by targeted RNA‐based NGS assays. Issue 8 (9th May 2020) - Kirchner, Martina; Glade, Julia; Lehmann, Ulrich; Merkelbach‐Bruse, Sabine; Hummel, Michael; Lehmann, Annika; Trautmann, Marcel; Kumbrink, Jörg; Jung, Andreas; Dietmaier, Wolfgang; Endris, Volker; Kazdal, Daniel; et al.
Abstract: Gene fusions involving the three neurotrophic tyrosine receptor kinase genes NTRK1, NTRK2, or NTRK3 were identified as oncogenic drivers in many cancer types. Two small molecule inhibitors have been tested in clinical trials recently and require the detection of a NTRK fusion gene prior to therapeutic application. Fluorescence in situ hybridization (FISH) and targeted next‐generation sequencing (tNGS) assays are commonly used for diagnostic profiling of gene fusions. In the presented study we applied an external quality assessment (EQA) scheme in order to investigate the suitability of FISH and RNA‐/DNA‐based tNGS for detection of NTRK fusions in a multinational and multicentric ring trial. In total 27 participants registered for this study. Nine institutions took part in the FISH‐based and 18 in the NGS‐based round robin test, the latter additionally subdivided into low‐input and high‐input NGS methods (regarding nucleic acid input). Regardless of the testing method applied, all participants received tumor sections of 10 formalin‐fixed and paraffin‐embedded (FFPE) tissue blocks for in situ hybridization or RNA/DNA extraction, and the results were submitted via an online questionnaire. For FISH testing, eight of nine (88.8%) participants, and for NGS‐based testing 15 of 18 (83.3%) participants accomplished the round robin test successfully. The overall high success rate demonstrates that FISH‐ and tNGS‐based NTRK testing can be well established in a routine diagnostic setting. Complementing this dataset, we provide an updated in silico analysis on the coverage of more than 150 NTRK fusion variants by several commercially available RNA‐based tNGS panels.